METHODOLOGICAL FOUNDATION OF STRATEGIC PLANNING IN THE RUSSIAN FEDERATION - O. V. Morozov; M. A. Vasiliev; A. G. Biryukov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article identifies methodological foundation for goal setting, horizon fixing and budget parameters of resource supply of strategic planning documents. The authors studied foreign and home works in the field of industrial construction, system genesis, structural analysis and quantitative modeling. They used quantitative methods of initial data processing, table methods of research results visualization. A method of finding the optimum values of distributing revenues of the consolidated budget of the Russian Federation among levels of the budget system. The three-level budget system of the country was analyzed as an institution, a tool and a resource source of strategic planning on federal and sub-national levels. The authors showed the necessity of drastic improvement of the institution of state programs in the Russian Federation and substantiated the rejection of single orders and decisions in favour of documents of strategic planning, they also recommended to toughen control over implementation of documents of strategic planning with obligatory consequences for their participants and documents themselves. It was grounded that achieving the optimum structure of the budget system (and movement in this direction) could create conditions necessary to include sub-national bodies of power in implementation of national projects and to realize various potentials of its regions, as a unique advantage of the Russian Federation.